2016
DOI: 10.1007/s10278-016-9875-z
|View full text |Cite
|
Sign up to set email alerts
|

Automated Lung Segmentation from HRCT Scans with Diffuse Parenchymal Lung Diseases

Abstract: Performing accurate and fully automated lung segmentation of high-resolution computed tomography (HRCT) images affected by dense abnormalities is a challenging problem. This paper presents a novel algorithm for automated segmentation of lungs based on modified convex hull algorithm and mathematical morphology techniques. Sixty randomly selected lung HRCT scans with different abnormalities are used to test the proposed algorithm, and experimental results show that the proposed approach can accurately segment th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…Noor et al [11] Framework including thresholding and morphology based segmentation coupled with feedback -----98.4% Pulagam et al [12] The modified convex hull approach and morphological operators -----98.62%…”
Section: Visual Results and Interpretationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Noor et al [11] Framework including thresholding and morphology based segmentation coupled with feedback -----98.4% Pulagam et al [12] The modified convex hull approach and morphological operators -----98.62%…”
Section: Visual Results and Interpretationsmentioning
confidence: 99%
“…In experiments, it was revealed that proposed method performed the segmentation with high DSC (98.4%). Pulagam et al [12] utilized the modified convex hull approach and morphological operators for segmentation. According to the experiments, proposed approach obtained 98.62% DSC on overall.…”
Section: Introductionmentioning
confidence: 99%
“…For over a decade, scholars from various strata of the globe have put forward a series of pulmonary lung nodule detection methods [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. The primary stages employed in these lung nodule detection methods are lung segmentation [4][5][6][7][8][9][10][11][12][13], nodule candidate detection [14][15][16][17][18][19], and elimination of false positive nodules (FPNs) [10,14,[19][20][21]. The first stage shows that lungs look like dark regions in CT scans, as they are basically bags full of air inside it, hence, the image intensities of the lung and surrounding tissues are clearly contrasted.…”
Section: Previous Workmentioning
confidence: 99%
“…To overcome these problems, a chain code representation method [10], morphological approaches [11], a rolling ball method [12] are used. In this paper a new contour correction method is proposed by using modified convex hull algorithm [13] for effective segmentation of lung region.…”
Section: Previous Workmentioning
confidence: 99%
“…It is estimated that by 2025, the number of people who die of lung cancer in China alone will be close to 1 million each year. Studies have shown that early detection and early treatment of lung cancer can effectively improve the survival rate of lung cancer patients: the 5-year survival rate increased from 14% to 49% [1]. CT imaging is one of the effective methods to help doctors diagnose lung diseases.…”
Section: Introductionmentioning
confidence: 99%